Disrupting white supremacy from within : white people on what we need to do - Harvey, Jennifer, 1971-; Case, Karin A., 1958-; Gorsline, Robin Hawley, 1946- (Cleveland : Pilgrim Press, 2004)
"Through careful, thoughtful examination of the nature and workings of race, racism, and white supremacy, the contributors - an all-white group of theologians, ethicists, teachers, ministers, and activists - have provided a resource that will help white people do their own work of confronting and understanding the impact of white supremacy in the malformation of their own souls, acknowledging its devastating effects on people of color, and taking their own steps toward its abolishment."--BOOK JACKET
Shaking the foundations : white supremacy in the theological academy / |r Robin Hawley Gorsline -- |t Claiming white social location as a site of resistance to white supremacy / |r Karin A. Case -- |t Race and reparations : the material logics of white supremacy / |r Jennifer Harvey -- |t Gaps and flashpoints : untangling race and class / |r Elizabeth M. Bounds -- |t What race is your sex? / |r Laurel C. Schneider -- |t El testigo verdadero libra las almas : the Central America Peace Movement and anti-racism / |r Becky Thompson -- |t "We make the road by walking" : reflections on the legacy of white anti-racist activism / |r Sally Noland Mac Nichol -- |t To hear and to be accountable : an ethic of white listening / |r Aana Marie Vigen -- |t Ceremonies of gratitude, awakening, and accountability : the theory and practice of multicultural education / |r Sharon D. Welch.
Includes bibliographical references.
Keywords: Racism -- United States; Whites -- Race identity -- United States; Whites -- Attitudes -- United States; Social movements -- United States; Christians -- Attitudes. -- United States; Racism -- Christianity. -- Religious aspects